2017
DOI: 10.1016/j.pmedr.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of sexual orientation and sleep disturbance among young adults

Abstract: We examined associations among 3 dimensions of sexual orientation (identity, attraction, and behavior) and sleep disturbance among young adults in the United States. Using Wave IV of the National Longitudinal Study of Adolescent Health (respondents aged 24–32, N = 14,334), we ran multivariate logistic regressions to estimate the probability of reporting trouble falling asleep, trouble staying asleep, and short sleep duration, based on specific sexual orientation categories.Results after controlling for mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Future research using larger samples could further examine pattern of sexual minority subgroup differences and potential transitions from one subgroup to another across time. 41 Third, the measure of sexual orientation was not available in Wave 7 and so it was not possible to examine the concurrent associations between sexual minority status and sleep behaviors at Wave 7. In light of research that shows the importance of fluidity of sexual identity, 7 it would be innovative to model changes in sexual identity and sleep behaviors over time in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Future research using larger samples could further examine pattern of sexual minority subgroup differences and potential transitions from one subgroup to another across time. 41 Third, the measure of sexual orientation was not available in Wave 7 and so it was not possible to examine the concurrent associations between sexual minority status and sleep behaviors at Wave 7. In light of research that shows the importance of fluidity of sexual identity, 7 it would be innovative to model changes in sexual identity and sleep behaviors over time in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Response options included are as follows: "never in the past 4 weeks," "less than once a week," "one or two times a week," "three or four times a week," and "five or more times a week." Consistent with prior studies evaluating chronic sleep disturbance using this measure in Add Health, we recoded both trouble falling and staying asleep into dichotomous variables: 0 (two times or less per week) or 1 (three times or more per week) [41].…”
Section: Sleepmentioning
confidence: 99%
“…Disparities in sleep problems between the LGB and general population have been documented in prior studies [ 25 , 29 31 ]. LGB individuals are more likely to report short sleep duration and other sleep problems, including snoring, sleep latency, and low sleep quality, compared to the general population [ 17 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 88%
“…Based on a previous study [ 30 ] the participant was considered to have a sleep dysfunction if they indicated ‘yes’ to any of the following more than three times a week: a) unable to sleep within 30 min (sleep latency), b) cough or snore loudly, c) waking up mid-sleep or too early, d) trouble staying awake during the day. Short sleep duration was defined as sleeping less than 6 hours on average in the past month [ 31 ], and is associated with increased risk of obesity, cardiovascular disease, stroke, and depression [ 47 ]. Sleep quality was rated on a 4-point scale from very bad to very good and responses were dichotomized into good or bad quality sleep.…”
Section: Methodsmentioning
confidence: 99%